2017
DOI: 10.1097/phm.0000000000000836
|View full text |Cite
|
Sign up to set email alerts
|

Walking Aids for Enabling Activity and Participation

Abstract: In this systematic literature review, we examined whether and how walking aids (i.e., canes, crutches, walkers, and rollators) enable activity and participation among adults with physical disabilities. Medline, Embase, all EBM reviews, PsychInfo, CINAHL, and Web of Science databases were used to identify studies published since 2008. Quantitative and qualitative designs were included. Data regarding participants, assistive device use, outcome measures, and domains of participation were extracted. Two reviewers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(33 citation statements)
references
References 29 publications
0
25
2
Order By: Relevance
“…This study showed that the acclimation process and acceptance of a spinal orthosis could be facilitated through proper fitting and information on how it worked, as well as how and when it could be best used. An acclimation process can also be seen in other types of assistive devices, such as walking aids, in which studies show that support and information are needed in order to make it easier for the individual to accept a new assistive device that makes daily activities easier [ 30 ]. One problem with the spinal orthosis was that it tended to ride up during physical work, particularly work above shoulder height.…”
Section: Discussionmentioning
confidence: 99%
“…This study showed that the acclimation process and acceptance of a spinal orthosis could be facilitated through proper fitting and information on how it worked, as well as how and when it could be best used. An acclimation process can also be seen in other types of assistive devices, such as walking aids, in which studies show that support and information are needed in order to make it easier for the individual to accept a new assistive device that makes daily activities easier [ 30 ]. One problem with the spinal orthosis was that it tended to ride up during physical work, particularly work above shoulder height.…”
Section: Discussionmentioning
confidence: 99%
“…Despite various existing walkers are owned by seniors, reported statistics show that 33% of people over 60 years fell at least once (Luz et al, 2017). We argue that intelligence is essential for an elderly walker to detect abnormal user behaviors and provide timely safety support, since primitive assistance devices, such as rollators and walkers, are much likely to fail (Bertrand et al, 2017). Exoskeleton (Tucker et al, 2019) is another approach with multiple robotic joints and links worn onto the user body, effective but less practical for daily wearing by older persons.…”
Section: Introductionmentioning
confidence: 92%
“…Limited reports of benefits from walking aid use to facilitate activity are available, but evidence suggests that nonweightbearing (NWB) ambulation to completely offload an injured lower limb using standard walking aids can cause axillary/hand pain or stance limb pain in 68% of users. 3,11,14 Major concerns are that walking aid selection may alter stance limb plantar force (SLPF), stepping frequency, and percentage of time weightbearing (% WB), and increase risk of injury. 7 Further, the increased physical demand of using standard walking aids, especially in older adults, negatively impacts user compliance and often results in patient discontinuance.…”
Section: Introductionmentioning
confidence: 99%